Type II mode of JAK2 inhibition and destabilization are potential therapeutic approaches against the ruxolitinib resistance driven myeloproliferative neoplasms - Gorantla, Sivahari P.; Prince, Gerin; Osius, Jasmin; Dinesh, Dhurvas Chandrasekaran; Boddu, Vijay; Duyster, Justus; von Bubnoff, Nikolas (Frontiers in Oncology, 2024)
Background Ruxolitinib has been approved by the US FDA for the treatment of myeloproliferative neoplasms such as polycythemia vera and primary myelofibrosis. Ruxolitinib will remain a main stay in the treatment of MPN patients due to its effective therapeutic benefits. However, there have been instances of ruxolitinib resistance in MPN patients. As JAK2 is a direct target of ruxolitinib, we generated ruxolitinib-resistant clones to find out the mechanism of resistance. Methods Cell-based screening strategy was used to detect the ruxolitinib-resistant mutations in JAK2. The Sanger sequencing method was used to detect the point mutations in JAK2. Mutations were re-introduced using the site-directed mutagenesis method and stably expressed in Ba/F3 cells. Drug sensitivities against the JAK2 inhibitors were measured using an MTS-based assay. JAK2 and STAT5 activation levels and total proteins were measured using immunoblotting. Computational docking studies were performed using the Glide module of Schrodinger Maestro software. Results In this study, we have recovered seven residues in the kinase domain of JAK2 that affect ruxolitinib sensitivity. All these mutations confer cross-resistance across the panel of JAK2 kinase inhibitors except JAK2-L983F. JAK2-L983F reduces the sensitivity towards ruxolitinib. However, it is sensitive towards fedratinib indicating that our screen identifies the drug-specific resistance profiles. All the ruxolitinib-resistant JAK2 variants displayed sensitivity towards type II JAK2 inhibitor CHZ-868. In this study, we also found that JAK1-L1010F (homologous JAK2-L983F) is highly resistant towards ruxolitinib suggesting the possibility of JAK1 escape mutations in JAK2-driven MPNs and JAK1 mutated ALL. Finally, our study also shows that HSP90 inhibitors are potent against ruxolitinib-resistant variants through the JAK2 degradation and provides the rationale for clinical evaluation of potent HSP90 inhibitors in genetic resistance driven by JAK2 inhibitors. Conclusion Our study identifies JAK1 and JAK2 resistance variants against the type I JAK2 inhibitors ruxolitinib, fedratinib, and lestaurtinib. The sensitivity of these resistant variants towards the type II JAK2 inhibitor CHZ-868 indicates that this mode of type II JAK2 inhibition is a potential therapeutic approach against ruxolitinib refractory leukemia. This also proposes the development of potent and specific type II JAK2 inhibitors using ruxolitinib-resistance variants as a prototype.